THE NEED ASSESSMENT OF INNOVATIVE LEADERSHIP DEVELOPMENT OF THE ADMINISTRATORS OF AFFILIATED SCHOOLS OF TRIAM UDOM SUKSA PATTANAKARN - รัตนรังสฤษฏ ตฤณเศรษฐ์; แช่มช้อย สุกัญญา (Academic Journal Phranakhon Rajabhat University, 2019)
The objective of this quantitative research was to study the need assessment of innovative leadership development of the administrators of affliated schools of Triam Udom Suksa Pattanakarn. The informants of this research were 148 people: school directors of affliated schools of Triam Udom Suksa Pattanakarn and the heads of every department from 17 schools. The questionnaire was chosen to be the research tool to get the information about the current situation and the desirable characteristics of innovative leadership development of the administrators of affliated schools of Triam Udom Suksa Pattanakarn. Statistical analysis such as frequency, percentage, mean, standard deviation and modifed priority needs index (PNI Modifed ,) were used to describe the obtained information. The need assessment of innovative leadership development of the administrators of affliated schools of Triam Udom Suksa Pattanakarn was summarized that had the modifed priority needs index as follows: The frst need assessment was creativity (PNI = 0.67). The second need assessment was teamwork (PNI = 0.66). And the third need assessment was vision to change, for the better (PNI = 0.65)